ANALISA PENGARUH KRISIS SUBPRIME MORTGAGE TERHADAP INDIKATOR RETURN SAHAM INDUSTRI KONSUMSI YANG TERDAFTAR DI BEI - Ridwan Zulpi Agha (TEKUN: Jurnal Telaah Akuntansi dan Bisnis, 2017)
The economic crisis of 2008, better known by the Subprime Mortgage crisis, greatly affecting the economic conditions and the capital markets at that time, especially for the economy and capital markets in the country where was the crisis came from, the U.S. and also in other developed countries, such as Japan Germany, France, etc. Behind of gloomy capital market conditions in some of these countries, there are still a few other countries that are not affected at all and even influence those that experience an increase in capital market transactions. According to economic experts, one of these countries is Indonesia, with one of the indications is that the share purchase transaction to the consumer sector firms in Indonesia was increased significantly. That's why this study was conducted to examine the effect of the economic crisis of 2008 to the indicators stock return sector consumption listed on Indonesia Stock Exchange (BEI). This study uses data of annual financial statements published by companies in the consumer sector from 2004 up to 2012. Analysis techniques used in this study is a multiple linear regression with different test of  an average value and test of different regression models. The results showed, there were significant differences in the regression model stock returns in the period before and after the economic crisis, and there was significant difference in the average value of the variable ROA and CR as a result of the economic crisis Subprime Mortgage